Indices of sarcopenic obesity are important predictors of finite element analysis-derived bone strength in older adults with obesity - Gregori, Giulia; Paudyal, Arjun; Barnouin, Yoann; Celli, Alessandra; Segoviano-Escobar, Martha Belen; Armamento-Villareal, Reina; Napoli, Nicola; Qualls, Clifford; Villareal, Dennis T. (Frontiers in Endocrinology, 2023)
Background. The expanding population of older adults with obesity is a public health challenge, in part, because of increased risk of fractures despite normal or high bone mineral density. Potential factors predisposing to fractures in this group include sarcopenia associated with obesity and impaired bone quality. We aimed to determine the contribution of sarcopenic obesity (SO) indices to bone strength as assessed by micro-finite element analysis (μFEA) of high-resolution peripheral quantitative computed tomography (HR-pQCT). One hundred eighty-nine older (age ≥ 65 yrs.) adults with obesity (BMI ≥ 30 kg/m 2 ) participated in lifestyle intervention trials at our medical center. All underwent baseline measurements of bone strength (failure load and stiffness) using μFEA from HR-pQCT of the distal radius and tibia. In addition, SO indices (appendicular lean mass/weight [ALM/W] and percent body fat [FM%]) by dual-energy x-ray absorptiometry and handgrip strength (HGS) by dynamometry) were assessed. SO was diagnosed and staged based on the 2022 ESPEN and EASO expert consensus statement. Results. Both ALM/W and HGS were positively correlated explaining 22% to 36% of the variance in failure load and stiffness at the distal radius and tibia (all p <0.001). In contrast, FM% was negatively correlated explaining 22% to 31% of the variance in failure load and stiffness at the distal radius and tibia (all p <0.001). The associations of SO indices with failure load and stiffness remained significant after controlling for age, sex, race/ethnicity, diabetes, and 25-oh vitamin d (ALM/W: R 2 = 0.301 to 0.448, HGS: R2 = 0.346 to 0.472, FM%: R2 = 0.279 to 0.432) (p <0.001 to 0.011). SO was diagnosed in 75/189 (40%) of participants with 66/75 (88%) having functional or metabolic complications (Stage II). Participants with SO had lower failure load and stiffness at the distal radius than participants with no SO (both p <0.05.) Conclusions. These findings demonstrate that lower muscle mass and strength and higher fat mass may impair bone quality. Therefore, interventions that focus on preserving muscle mass and strength while reducing fat mass may be important to decrease fracture risk when older adults with obesity undertake lifestyle therapy.